Ideas for retirement planning - Lee, Roland M.S. (2006)
When the time to retire is at hand, will you be able to afford it? This is a question that many Malaysians need to face. The financial requirements can be daunting as it is also dependent on the life-style of choice. To enjoy a life-style of choice during retirement years requires much forward-planning. It cannot be left too late before retirement sets in. For example, even five years before retirement starts will be inadequate time to accumulate sufficient retirement funds. Afterall, life during retirement may last as long as the time one spent as a working adult.